Nano- e microfitoplâncton da Baía de Guanabara (RJ, Brasil) em condições tróficas distintas: aspectos estruturais e pré-funcionais - Santos, Viviane Severiano dos (2002)
Presents the space-time variations for the nano- and microphytoplankton of Guanabara Bay, Rio de Janeiro, Brazil, focussing on the structure (composition and abundance) and pre-functional (auto and heterotrophic components, biomass) aspects of the community. Sampling strategy included intensive sampling (weekly) for two and a half years (July/1998 - December/2000), at 0.5 m, at two sites with different water qualities: Urca (close to the entrance) e Ramos (inner-reaches). The abundance of the phytoplankton was one order of magnitude higher at Ramos, where cell density of autotrophs varied around 10^7 - 10^9 cells. L^-1 for the nanoplankton and 10^5 - 10^7 cells. L^-1 for the microplankton, while biomass values varied around 10^2 - 10^3 μgC. L^-1 and 10 - 10^3 μgC. L^-1, respectively. At Urca, lower relative and absolute abundances of heterotrophs were also found. The species list for the microphytoplankton included 168 taxa for Urca and 69 for Ramos; diatoms were the best-represented species, followed by dinoflagellates. For the nanophytoplankton, it was identified just some groups (diatoms, dinoflagellates, cryptophytes and cyanobacteria) due to methodology of analysis (just epifluorescence). Median diversity of microphytoplankton was 2.43 bits.ceff^-1 at Urca and 1.68 bits.celr^-1 at Ramos. Trophic state (meso-eutrophic for Urca and hypertrophic for Ramos) and salinity (lower at Ramos) were identified as the main forcings determining the space variation found for the phytoplankton. Seasonal variations were associated to a rainny summer (dominance of diatoms and cyanobacteria) and a dryer winter (increase on the contribution of flagellates). The stronger seasonal variation found for Ramos was attributed to the greater influence of direct river flow to this area. Interannual variations coincided with the occurrence of "La Niña" years (1998 and 1999) when seasonal variations were different from those considered as the pattern for Guanabara Bay. Weekly variations were detected, especially for dinoflagellates and euglenophytes from the innerreaches of the bay, the area under stronger environmental stress. Estimates of total biomass from cell biovolume showed that the contribution of the microphytoplankton was equivalent and, at time, even greater than that of the nanoplankton, in contrast to what was indicated by the cell density data. Moreover, the heterotrophic componentes of nanoplankton were less abundant in terms of biomass, while the opposite occurred for microplankton ones. Biomass in terms of carbon, while still providing a sinoptic scenario of the community, was very important to determine the true contribution of each fraction (nano:microphytoplankton) and of each component (auto:heterotrophs), which were key to support the trophic states determined for Guanabara Bay.